Pola Komunikasi Organisasi Majelis Talim Syubbanul Muslimin Dalam Pembentukan Karakter Sosial Pada Remaja - Nugroho, Hussein Adi; Ichsan, Muhammad; Lukman, Lukman (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research is motivated by the importance of organizational communication patterns carried out by religious assemblies in shaping the social character of adolescents. The aim of this study is to understand the role and factors of organizational communication in facilitating social interaction and character development, as well as to gain an understanding of adolescents' responses and perceptions of the communication patterns implemented. The theories used in this research are organizational communication theory, communication patterns, and adolescent character formation. The method used is descriptive qualitative. Data collection techniques were conducted through informant interviews and documentation studies. The results of the study indicate that the Syubbanul Muslimin Assembly acts as a religious education center that provides positive benefits for adolescents. The communication patterns applied by the Syubbanul Muslimin Assembly are effective in conveying religious values and social norms. Interactions within the organization contribute to the development of adolescents' social personalities.